Generic versus innovator: Analysis of the pharmaceutical qualities of paracetamol and ibuprofen tablets in the Nigerian market (2009)
The physicochemical equivalence of twenty-two brands of paracetamol and nine brands of ibuprofen tablets sourced from retail Pharmacy outlets in the Nigerian market to their respective innovator brands were investigated. The uniformity of weight, friability, crushing strength, disintegration and dissolution times and assay of active paracetamol ingredient were used as assessment parameters. All the brands of paracetamol and ibuprofen tablets complied with the official specifications for uniformity of weight. However, five brands of paracetamol failed the friability test, one brand of paracetamol and two brands of ibuprofen failed the disintegration test and three brands of paracetamol and four brands of ibuprofen failed the assay of active ingredients. The study shows that not all the brands of paracetamol and ibuprofen tablets are physico-chemically equivalent to their innovator brands. There is therefore the need for constant market surveillance to ascertain their compliance with official standards and equivalence to the innovator products.